Pertumbuhan Ekonomi Indonesia di Era New Normal - Shahrul, Shahrul (Lembaga Yasin AlSys, 2024)
This research examines the phenomenon of Indonesia's economic growth in the context of the New Normal era. This era is marked by significant changes in daily life, especially in response to the global pandemic that has hit the world. The main focus of this research is to analyze the impact of the New Normal on Indonesia's economic growth, taking into account changes in consumption patterns, adaptation of the business sector, and economic policies implemented by the government. This research method involves analyzing macroeconomic data, opinion surveys, and case studies to understand changes in consumer behavior, business strategies, and economic policies taken by the government. The research results show that Indonesia, like other countries, experienced a significant economic transformation during the New Normal period. Although there are challenges such as a decline in economic activity in several sectors, this research also identifies new opportunities that are emerging, especially in the digital and sustainable sectors. In addition, this research provides policy recommendations for the Indonesian government to strengthen and accelerate economic recovery amidst the New Normal. These recommendations include strengthening digital infrastructure, increasing investment in sustainable sectors, as well as developing policies that support digital transformation and sustainable business adaptation. It is hoped that this research can contribute to stakeholders, researchers and policy makers in understanding the dynamics of Indonesia's economic growth in the New Normal era, as well as providing a basis for developing strategies to face this challenging future.